2004
DOI: 10.1158/0008-5472.can-03-3657
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoid Antagonist MX781 Induces Clusterin Expression in Prostate Cancer Cells via Heat Shock Factor-1 and Activator Protein-1 Transcription Factors

Abstract: Retinoids mediate numerous biological responses through the transcriptional activation of nuclear retinoid receptors. Due to their antiproliferative activity, retinoids have shown promise as anticancer agents. Synthetic analogs have been described that selectively activate one subset of the retinoid receptors or inhibit their transcriptional activity. Some of these compounds exhibit strong anticancer activity, which is associated with their ability to induce apoptosis. Here we describe that the retinoid antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…For example, heat shock factor-1 (HSF-1) is a well-known regulator of CLU expression by binding CLE sites in CLU promoter regions (39). In addition, AP-1 and Egr-1 also regulate CLU expression (13,40). Furthermore, we recently reported that Y-box binding protein-1 is a key transcriptional factor that induces CLU expression during endoplasmic reticulum stress (15).…”
Section: Discussionmentioning
confidence: 99%
“…For example, heat shock factor-1 (HSF-1) is a well-known regulator of CLU expression by binding CLE sites in CLU promoter regions (39). In addition, AP-1 and Egr-1 also regulate CLU expression (13,40). Furthermore, we recently reported that Y-box binding protein-1 is a key transcriptional factor that induces CLU expression during endoplasmic reticulum stress (15).…”
Section: Discussionmentioning
confidence: 99%
“…sCLU was induced by Ն2 cGy in various breast and colon cancer cells, with peak induction of sCLU noted 24 -72 h after IR, as measured by promoter activity, transcript, and protein levels (7). Although specific transcription factors have been implicated in sCLU regulation after specific genotoxic stresses, including repression by c-Fos (25) and possible activation by c-Myc (19) and AP-1 (26), the signaling pathways involved and transcription factors that directly regulate the expression of this gene after IR have not been elucidated.…”
Section: Ionizing Radiation (Ir)mentioning
confidence: 99%
“…sCLU interacts with and inhibits conformationally-altered Bax in response to cytotoxic stress thereby impeding Bax oligomerization, cytochrome C release, and intrinsic pathway activation (2). sCLU is transcriptionally activated by heath shock factor (HSF-1) (3, 4) and increased levels are associated with a broad range of normal and disease states including aggregopathies in Alzheimer’s Disease (5), mammary gland involution (6) and treatment resistance in cancer. In cancer, sCLU is highly expressed in cells surviving apoptotic stimuli and in advanced and treatment resistant cancers (7), and protects cells against apoptosis in response to hormone-, radiation-, and chemo-therapy (7–9).…”
Section: Introductionmentioning
confidence: 99%